The structure of the momentum of basketball games sensed by point guard players with excellent competitive ability - Nakase, Y.; Sano, A. (Japan Journal of Physical Education, Health and Sport Sciences, 2017)
The purpose of this research was to clarify the structure of the momentum of basketball games as sensed by point guard players with excellent ability from the "Bewegungslehre des Sports" viewpoint in order to improve the tactical ability of basketball players. The study involved an interview survey of three such players. After considering the structure or the momentum of games, the following points became clear. 1. The players are aware that "continuity" and "compulsion" form the nature of game momentum. These two characteristics are seen as both Good and Bad momentum. 2. "Player's feelings" were listed as one of the facets of game momentum. As a means of optimizing such feelings, priority was given to player encouragement and selection of tactics to make the game exciting. 3. "Play based on common tactical intention" was listed as another facet of game momentum. Games developed with such intention had the strongest possibility of winning, and the players considered that practicing it (or preventing the other team from doing so) without any difference in tactical intention created momentum. 4. "Player's feelings" and "play based on common tactical intention", which contribute to momentum, were considered to be not independent but interactive. 5. As a result, it was clarified that "players' feelings" is a factor that can directly generate "game momentum" and that "game-related events" and "player's sense of value" are factors that can influence each other and are interdependently structured.